Pengaruh remote audit terhadap kualitas internal audit BUMN - Erwin Gusdiana Erwin Gusdiana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
BUMN is a State-Owned Enterprise where the capital owned is partly or even wholly owned by the state. BUMN have an important role in improving the country's economy. Therefore, the state must be able to observe and monitor the progress of BUMN so that they are at quality financial performance. BUMN financial analysis is carried out through audit activities carried out by internal auditors or external auditors. One of the audit methods used is remote audit, where this is carried out at a different location or online based. For this reason, researchers want to find out more about the effect of implementing remote audits on the quality of BUMN internal audits. The purpose of this study is to obtain information about the presence or absence of the influence of remote audits on the quality of BUMN internal audits. The method used is qualitative by collecting data through collecting various research results with a relevant research focus. The data obtained will be analyzed in depth to find out the results of the research. The results of the study show that remote audits have a positive and significant effect on improving the quality of BUMN  internal audits.